Abstracts from international Emergency Medicine journals. Issue 12 (18th November 2016) - Weber, Ellen J
Abstract : Editor's note: EMJ has partnered with the journals of multiple international emergency medicine societies to share from each a highlighted research study, as selected by their editors.